The Rambler Club's Gold Mine - Sheppard, W. Crispin (William Crispin), 1871- (Salt Lake City, UT : Project Gutenberg, 2022)
"The Rambler Club's Gold Mine" by W. Crispin Sheppard is a children's adventure novel written in the early 20th century. The story centers on a group of boys known as the Rambler Club, who embark on a quest for a legendary gold mine after being entrusted with its secret by Wanatoma, an aged Indian warrior, in gratitude for saving his life. Their journey promises excitement, challenges from nature, and the test of their courage and resourcefulness against possible dangers. The opening of the adventure sets the stage as the boys gather in their cabin, discussing their plans for the expedition while showcasing their camaraderie and playful banter. They express their enthusiasm for the search, though not without some comic relief from their doubts and fears. As they prepare to leave, the narrative hints at both the lighthearted nature of their friendship and the serious undertones of potential danger lurking in the wilderness and from other men who may seek the gold for themselves. The first chapter concludes with an introduction to various characters, including the boys and the stern lumbermen, suggesting a larger world filled with both allies and foes as they pursue their treasure-hunting quest. (This is an automatically generated summary.)
Illustrated by the author.
Release date is 2022-03-18
David Edwards, Mary Meehan and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Adventure stories; Gold mines and mining -- Juvenile fiction; Boys -- Societies and clubs -- Juvenile fiction; Washington (State) -- Juvenile fiction